2008
DOI: 10.1111/j.1365-2354.2007.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Involving people affected by cancer in research: a review of literature

Abstract: The purpose of the literature review was to find out why people affected by cancer have been involved in research; how they have been involved and the impact of their involvement. We used systematic methods to search for literature, applied inclusion and exclusion criteria, conducted a quality appraisal, selected relevant data from the included articles for analysis, and provided a narrative summary of these data. The literature shows that people affected by cancer, particularly women with breast cancer, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 45 publications
0
55
0
3
Order By: Relevance
“…Lay members from six of the nine organisations volunteered to participate in the study. The median length of time involved in PPI activities was 4 years (range [3][4][5][6][7][8][9][10][11][12][13][14]. Participants were engaged in a median of 5 PPI activities (range 2-8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lay members from six of the nine organisations volunteered to participate in the study. The median length of time involved in PPI activities was 4 years (range [3][4][5][6][7][8][9][10][11][12][13][14]. Participants were engaged in a median of 5 PPI activities (range 2-8).…”
Section: Resultsmentioning
confidence: 99%
“…This political mandate is one reason for the rise of PPI in health research; other reasons include the consequentialist, epistemological and moral arguments (Boote, 2010). The consequentialist argument is outcome oriented and asserts that PPI in research improves the quality, credibility and relevance of the research design, process and findings (Hubbard, 2007; Lindenmayer, 2007; Sutton, 2008). The other arguments are process oriented with the epistemological argument emphasising the importance of experiential knowledge provided by patients and the public, and the moral argument highlighting the importance of democratic representation and the empowerment of disadvantaged groups (Boote, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Factors promoting the involvement of users in research have been reported to include ‘good working relationships’ between professional researchers and service users enabled by mutual respect and an effort on the part of researchers to promote equality in the face of a relationship characterized by an imbalance of power 10 . A structured approach has been advocated, with appropriate training of service users to enable them to understand and take part in research development and conduct 11 . Paying citizens who are involved in research is a contested issue but some have identified this as an enabler of user involvement 12 .…”
Section: Introductionmentioning
confidence: 99%
“…While this was to be expected, as abstract and text appraisals are standard practice for determining relevance in many SRs (Campbell et al 2003;Dixon-Woods et al 2007;Higginbottom et al 2012;Hubbard, Kidd, and Donaghy 2008), such a transparent search for and selection of articles have been noted as wanting in reviews of argument-based literature (McCullough, Coverdale, and Chervenak 2007). We were able to transparently identify, classify, analyse and process prescriptions from a literature that spanned medical and social sciences in a rigorous, comprehensive and transparent manner.…”
Section: Aspects That Transferred Wellmentioning
confidence: 99%
“…We drew on these relevant elements to synthesise a method that, we hoped, was reliable, would support inferences from text to real-world practice, which retained context, and which could be applied to a heterogeneous and multinormative literature. The method we developed for aggregation drew on cross-case techniques (Miles and Huberman 1994), narrative summary (Hubbard, Kidd, and Donaghy 2008;Secomb 2008) and metastudy (Paterson et al 2001). Narrative summary was chosen because the source articles were heterogeneous and lacked a common structure.…”
Section: Second Synthesismentioning
confidence: 99%